Optimalisasi Manajemen Berbasis Sekolah di Era Merdeka Belajar - Darmawan, I Putu Ayub; Wenas, Maria Lidya; Kurniawan, Aran Hendri; Purwanto, Harry (Fakultas Ilmu Keguruan dan Pendidikan, Universitas Kristen Indonesia, 2022)
The development of the world of education now continues to strive to improve the quality of the implementation of the learning process to produce graduates who can compete in the world of work, and have creativity and critical thinking skills. The government also plays a role in improving the quality of school management through decentralization of education in the form of school-based management and the provision of an independent learning curriculum. The aim of independent learning is the development of superior quality human resources. Therefore, this article aims to answer the question of how to optimize school-based management in the era of independent learning. The purpose of this study is to describe the optimization of school-based management in the era of independent learning. The research method used is a literature study by exploring various data sources and the results of research that has been carried out on school-based management and the independent learning curriculum. The results showed that school-based management supports the process of implementing learning in improving the quality of education in Indonesia. By taking into account the current educational curriculum, freedom of learning, becomes a guideline for managers of educational institutions to produce graduates of superior quality. Two important aspects of school-based management in improving the quality of education are managerial aspects and learning aspects.